2020
DOI: 10.1021/acsomega.9b03555
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated Methionine γ-Lyase: Application in Enzyme Prodrug Therapy of Pseudomonas aeruginosa Infection

Abstract: Lung disease caused by Pseudomonas aeruginosa is the leading reason for death in cystic fibrosis patients. Therapeutic efficacy of the pharmacological pairs, the naked/encapsulated mutant form of Citrobacter freundii methionine γ-lyase and the substrates, sulfoxides of S-substituted L-cysteine, generating thiosulfinates, was evaluated on the murine model of experimental sepsis caused by the multidrug-resistant P. aeruginosa 203-2 strain. The pairs containing the naked enzyme and substrates did not have antibac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…We have shown that the inclusion of C115H MGL into polyionic vesicles significantly improved its pharmacokinetic characteristics . Therapeutic efficacy of the “pharmacological pairs” composed of C115H MGL PICsomes and the substrates S -substituted l -cysteine sulfoxides has been demonstrated against the murine model of experimental sepsis caused by the multidrug-resistant Pseudomonas aeruginosa 203–2 strain …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…We have shown that the inclusion of C115H MGL into polyionic vesicles significantly improved its pharmacokinetic characteristics . Therapeutic efficacy of the “pharmacological pairs” composed of C115H MGL PICsomes and the substrates S -substituted l -cysteine sulfoxides has been demonstrated against the murine model of experimental sepsis caused by the multidrug-resistant Pseudomonas aeruginosa 203–2 strain …”
Section: Introductionmentioning
confidence: 98%
“…27 Therapeutic efficacy of the "pharmacological pairs" composed of C115H MGL PICsomes and the substrates S-substituted L-cysteine sulfoxides has been demonstrated against the murine model of experimental sepsis caused by the multidrug-resistant Pseudomonas aeruginosa 203−2 strain. 28 Here, we studied the influence of the molecular weight of polyaspartic acid (pAsp) and polylysine (pLys), their concentration, enzyme concentration, and availability of dextran on the PICsome size, their tendency to agglomerate, encapsulation degree of the enzymes, and their release from the vesicles. Steady-state parameters of the βand γelimination reactions catalyzed by encapsulated mutant enzymes were determined.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, to succeed in the production of the enzyme prodrug therapy for anticandidal therapeutic purposes, we propose to use another closely related to alliinase enzyme (Figure 1). Recently, we have shown that a binary system of methionine γ-lyase (EC 4.4.1.11, MGL)/S-alk(en)yl-L-cysteine sulfoxides possesses antimicrobial activity in vitro and in vivo [13,14]. This system generates antipathogenic compounds both from natural sub- Recently, we have shown that a binary system of methionine γ-lyase (EC 4.4.1.11, MGL)/S-alk(en)yl-L-cysteine sulfoxides possesses antimicrobial activity in vitro and in vivo [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that a binary system of methionine γ-lyase (EC 4.4.1.11, MGL)/S-alk(en)yl-L-cysteine sulfoxides possesses antimicrobial activity in vitro and in vivo [13,14]. This system generates antipathogenic compounds both from natural sub- Recently, we have shown that a binary system of methionine γ-lyase (EC 4.4.1.11, MGL)/S-alk(en)yl-L-cysteine sulfoxides possesses antimicrobial activity in vitro and in vivo [13,14]. This system generates antipathogenic compounds both from natural substrates and from their synthetic analogues, and the core enzyme can maintain its activity at the targeted surface via encapsulation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, antibiotic-free nanoreactors have recently been designed, based on the in situ conversion of prodrugs. For example, the conversion of (±) S -alk­(en)­yl- L -cysteine sulfoxides into antibacterial thiosulfinates have shown promise as a treatment against P. aeruginosa . Nanoreactors, and other catalytic systems, utilizing the activity of GOX and peroxidase enzymes (or mimics) represent a particularly effective antibacterial strategy against various species of Gram-positive and Gram-negative bacteria, producing reactive antimicrobial species such as H 2 O 2 , – OCl, or hydroxyl radicals ( • OH) in response to the presence of glucose. ,, However, using simple, well-defined systems and achieving controlled and local action of such nanoreactors remains challenging.…”
mentioning
confidence: 99%